Bartonella vinsonii subsp. berkhoffii and B. henselae in dogs - Müller, A.; Soto, F.; Sepúlveda, M.; Bittencourt, P.; Benevenute, J. L. [UNESP]; Ikeda, P. [UNESP]; Machado, R. Z. [UNESP]; André, M. R. [UNESP] (Cambridge University Press (CUP), 2018)
This study aimed to molecularly survey Bartonella in dogs from Chile. Quantitative real-time PCR (qPCR) for Bartonella spp. based on nuoG gene was performed in 139 blood samples taken from dogs belonging to rural localities of the Valdivia Province, Los Ríos region, southern Chile. nuoG qPCR-positive samples were submitted to conventional PCR assays for ftsZ, gltA, rpoB and nuoG genes and sequencing for speciation and phylogenetic analysis. Based upon qPCR results, Bartonella spp. occurrence in dogs was 4.3% (6/139). Out of six nuoG qPCR-positive samples, six, three, two and none showed positive results in cPCR assays based on gltA, ftsZ, rpoB and nuoG genes, respectively. Consistent sequencing results were obtained only for the ftsZ gene from sample #1532 (GeneBank accession number: MG252491), and gltA gene from samples #1535 (MG252490) and #1532 (148 bp fragment that was not deposited in GenBank). Phylogenetic analysis of ftsZ and gltA genes allowed speciation of two nuoG-positive samples, one as Bartonella vinsonii subsp. berkhoffii and the other as B. henselae. Bartonella vinsonii subsp. berkhoffii and B. henselae are detected for the first time in dogs from Chile, highlighting the importance of the canine population as a source of zoonotic agents and potential infection risk to humans.
Keywords: Bartonella spp; Chile; PCR